Three phase dry-type distribution transformers 50 Hz, from 100 kVA to 3 150 kVA, with highest voltage for equipment not exceeding 36 kV. Determination of loadability of a transformer loaded with non-sinusoidal current Part 2, (31st July 2013) - British Standards Institution,
No abstract available